Deskripsi Organizational Citizenship Behavior Perawat Untuk Lansia Di Wisma Harapan Asri Yayasan Mardiwijana Semarang” - Yulius Susilo; Rudy Elyadi (Praxis : Jurnal Sains, Teknologi, Masyarakat dan Jejaring, 2021)
The number of elderly population in Indonesia from year to year is increasing, so it is needed a place and assistance services for elderly citizens. Wisma Harapan Asri Semarang provides services so that the elderly residents feel comfortable and at ease. The nurses for the elderly have the role of assisting and serving elderly citizens. The performance of the nurses has an important role for the quality of the services of the elderly homestead. Improved services will be better if the nurses have the attitude and actions of the Organizational Citizenship Behavior (OCB) at work.This study aimed to determine the OCB of nurses based on five dimensions of OCB. The five dimensions of OCB according to Organ are: altruism, courtesy, conscientiousness, sportmanship, and civic virtue. Descriptive qualitative research method to describe the OCB actions of nurses. The results showed OCB of nurses in the high category. An effort to improve the performance of nurses in accordance with the five dimensions of OCB. Also efforts to improve the services of nurses to meet the needs of the elderly. This research is useful for Wisma Harapan Asri in an effort to shape the behavior of nurses to provide the best service for the elderly.